Pharmacognostical study of Powder of Heartwood of Pterocarpus santalinus L. f. - Swar, Sangeeta (Journal of Plant Resources, 2008)
Present paper deals with the pharmacognostical study of the powder of heartwood of Pterocarpus santalinus L.f., for its identification and to distinguish it from its adulterants. The study includes macroscopic, microscopic and preliminary physicochemical investigation Keywords: Pterocarpus; santalinus; Pharmacognostical characterization; microscopic character; florescence character; physico-chemical charactes; heartwood. Bulletin of the Department of Plant Resources Vol. 30, 2008. pp 95-96